The Role of Psychological Distance in Influencing Pro-environmental Behavior Spread: Perceived Justice Enforceability as a Moderator - Xu, Zhengquan; Cao, Qinren; Li, Shuang (Frontiers in Psychology, 2020)
The loose social system (MLSS) can spread tightly coupled complex practices under the context that members of it do not have the shared experience that enables coordination in longstanding tight formal organizations. To promote understanding of such process, we draw on the organizational justice literature and the perspective of justice enforceability, and construal level theory, given the possibility for other members in the MLSS to cheat to adopt pro-environment behavior, develop a conceptual model in which the impact of social members’ perceived psychological distance on their response to other social members adoption of pro-environmental behaviors is contingent on the on their perception of justice enforceability and cognitive appraisals (positive, not significant) towards the adoption of pro-environmental behaviors. We find that when the level of cognitive appraisals of social members is high, and they perceive that adoption of pro-environment behaviors is justice-enforceability, then the more proximal of the psychological distance they perceive, the stronger they will react to other social members’ adoption of pro-environmental behaviors. Further, they will adopt and enact such behavior, otherwise, they will be unwilling to adopt and enact such behavior. So, uneven psychological distance perception of social members can harm their adoption and spread of pro-environment behavior. We tested our model in the survey study. Results show that the proposed model is supported, and our understanding is enhanced about how social members’ willingness to adopt and spread pro-environment behavior is contingent on their perceptions of justice enforceability. Thus, the results of this research contribute to knowledge on the adoption and spread of pro-environment behaviors in the loose social system.